(untitled) (Ustozlar uchun, 2026)
Motivation is a key factor that influences the success of language learning. It affects learners’ effort, persistence, and overall achievement. Motivated students are more willing to participate in activities, practice regularly, and overcome difficulties during the learning process. There are two types of motivation: intrinsic, which comes from personal interest and enjoyment, and extrinsic, which is driven by external rewards such as grades, praise, or career opportunities. Both types play an essential role in language acquisition. Teachers also have a significant impact on learners’ motivation by creating a positive classroom environment, using engaging methods, and providing constructive feedback. Therefore, strong motivation is crucial for effective and successful language learning.